Improving the Performance of Educators with the Effectiveness Level of Additional Employee Income (TPP) in Junior High Schools: Peningkatan Kinerja Tenaga Pendidik Dengan Tingkat Efektivitas Tambahan Penghasilan Pegawai (TPP) Di Sekolah Menengah Pertama - Suciati, Detik; Rodiyah, Isnaini (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to describe and analyze the effectiveness of Additional Employee Income (TPP) in improving the performance of educators at the State Junior High School 2 Wonoayu, Sidoarjo Regency. To analyze the supporting factors and inhibiting factors of Additional Employee Income (TPP) in improving the performance of educators at the State Junior High School 2 Wonoayu, Sidoarjo Regency. The method that the author uses in this research is a quantitative descriptive method. The sample in this study were 46 educators. Validity test using Product Moment correlation from Pearson. The results of this study indicate that the effectiveness of the additional employee income program (TPP) in improving the performance of educators at the State Junior High School 2 Wonoayu Sidoarjo, is in the effective category, because based on the overall calculation of the indicators the questionnaire distributed contains 23 (twenty three) statements with the position of the number of Effectiveness of the additional employee income program (TPP) is 4987 which is in the interval >Q2 to Q3 with a value of >2645 – 5290 which is categorized as effective.Keywords: Effectiveness, Additional Employee Income (TPP), Performance Improvement